2016
DOI: 10.5902/1980509825106
|View full text |Cite
|
Sign up to set email alerts
|

REDUÇÃO DA ADUBAÇÃO E MELHORIA DAS CARACTERÍSTICAS DO SUBSTRATO COM O USO DO HIDROGEL NA PRODUÇÃO DE MUDAS DE <i>Eucalyptus dunnii</i> Maiden

Abstract: RESUMOO objetivo do estudo foi avaliar se a presença do hidrogel afeta as propriedades físicas e químicas do substrato e a relação do hidrogel com doses de adubação no desenvolvimento de mudas. No substrato com presença e ausência do hidrogel foi realizada análise de características químicas e físicas. A produção de mudas foi conduzida em casa de vegetação sob irrigação reduzida, utilizando delineamento inteiramente casualizado em arranjo bifatorial 2 x 6, em que os níveis do fator "A" referiram-se a presença … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 2 publications
(3 reference statements)
4
13
0
Order By: Relevance
“…This result indicate that the irrigation depth applied to the substrate with hydrogel was readily available to the seedlings. Navroski et al (2016) found larger SBD when using gel on the substrate or soil, and explained this result by the improved water retention and use by plants.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…This result indicate that the irrigation depth applied to the substrate with hydrogel was readily available to the seedlings. Navroski et al (2016) found larger SBD when using gel on the substrate or soil, and explained this result by the improved water retention and use by plants.…”
Section: Resultsmentioning
confidence: 89%
“…Similar result was found during the vegetative development of sweet pepper plants with the use of hydrogel (TITTONELL; GRAZIA; CHIESA, 2002). Navroski et al (2016), and Bernardi et al (2012) evaluated the use of hydrogel (6 g L -1 ) for the production of eucalyptus seedlings and found that the use of hydrogel favored the development of the seedlings, reducing the requirement of nutritional supplementation in about 20%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results corroborate those obtained by Navroski et al (2015) and Felippe et al (2016) on the production of the genus Eucalyptus seedlings. The increase in biomass with the addition of water-retaining polymer occurs due to the reduction of percolation of irrigation water and improvement in the aeration and drainage in soil (Bernardi et al, 2012) as well as the reduction in nutrient leaching (Navroski et al, 2015), which contributes directly to the improvement of the nutritional status of the plant, reducing the consumption of fertilizers from 25% to 50% (Navroski et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the use of synthetic conditioners is reported to contribute toward an increase in the water retention capacity of the substrate, which reduces the frequency of irrigation, and thus, allows more effective use of resources from the culture medium and water, which ultimately optimizes crop yield (Navroski et al, 2015). Moreover, the use of water-retaining polymers improves the chemical and physical characteristics of the substrate, allowing better utilization of the nutrients incorporated into the culture medium (Felippe et al, 2016;Navroski et al, 2016) This investigation sought to identify the influence of different watering regimes and the addition of water-retaining polymer to the substrate on the initial growth and metabolic processes of E. contortisiliquum seedlings. The main questions that we aimed to answer are: a) Is the growth of E. contortisiliquum seedlings dependent on the watering regime adopted?…”
Section: Introductionmentioning
confidence: 99%